Preoperative detection of the TERT promoter mutations in papillary thyroid carcinomas. (28th July 2021) - Nakao, Tomoe; Matsuse, Michiko; Saenko, Vladimir; Rogounovitch, Tatiana; Tanaka, Aya; Suzuki, Keiji; Higuchi, Miyoko; Sasai, Hisanori; Sano, Tsutomu; Hirokawa, Mitsuyoshi; Miyauchi, Akira; Kawakami, Atsushi; et al.
Abstract: Objective: Telomerase reverse transcriptase promoter ( TERT ‐p) mutations are strongly associated with tumour aggressiveness and worse prognosis in papillary thyroid carcinomas (PTCs). Since the TERT ‐p mutations have been reported to be subclonal, it is unclear how accurately they can be detected by preoperative fine‐needle aspiration (FNA). The objective of this study was to analyse the concordance rate of the TERT ‐p mutations between preoperative FNA and corresponding postoperative surgical specimens. Design and Patients: Ninety‐six cases of PTC aged 55 years or older were studied. The mutational status of TERT ‐p was detected by droplet digital polymerase chain reaction assay. Results: The mutational status of the TERT ‐p in FNA samples was highly concordant with that in postoperative formalin‐fixed and paraffin‐embedded (FFPE) specimens. The TERT ‐p mutation was significantly associated with age, tumour size, extrathyroidal extension and the Ki‐67 labelling index in multivariate analysis in both FNA and FFPE samples. Conclusions: The detection of the TERT ‐p mutations using FNA samples has a good ability to predict disease aggressiveness and, therefore, could be clinically useful in the determination of PTC management.